Low back pain: shifting the paradigm from non-specific to specific - Aremu, Oluwasegun A. (International Journal of Research in Orthopaedics, 2025)
Low back pain is a leading cause of disability worldwide and it imposes huge economic burden on affected individuals and the government. It can be broadly classified into specific and non-specific low back pain. Non-specific low back pain constitutes about 90% of all low back pain, and it is now a leading cause of years lived with disability. The present review aims to describe the evolution of the term non-specific low back pain, to show that the term may no longer be appropriate and to propose hypothesis that can explain low back pain in general. A review of the literature shows that several terms have been used to describe non-specific low back pain. Examples of such terms are mechanical low back pain, and idiopathic low back pain with few inconsistencies in the usage of the term. The term, non-specific low back pain, became widely accepted after introduction of the concept “diagnostic triage” by Waddell in 1994. The concept classified low back pain into specific, radicular syndrome and non-specific. As explained by Waddell, only radicular syndrome and specific types of low back pain require further diagnostic evaluation. This has been the practice ever since. Recent evidence from MRI findings of symptomatic and asymptomatic individuals however, suggest that diagnostic evaluation, coupled with specific provocation tests can lead to specific diagnosis of low back pain in majority of the cases. Based on these recent evidences and others, it can be hypothesized that low back pain is a spectrum of disease with a specific cause.